PENAFSIRAN HAKIM TERHADAP KETENTUAN PIDANA MINIMUM KHUSUS DALAM UNDANG-UNDANG TINDAK PIDANA KORUPSI - Ismail Rumadan (Jurnal Hukum dan Peradilan, 2013)
The spirit of the rule of law against corruption which is considered as an extraordinary crime that resulted in the occurrence of social inequality , the economy , the loss of faith in government and a variety of other problems that led to the birth of Law No. 31 of 1999 in conjunction with the Law No. 20 Year 2001 About Follow Corruption. The interesting thing about the formation of the Anti- Corruption Act is a criminal provision in the formulation of minimum deliknya against perpetrators of corruption . It is certainly different from the general criminal provisions in the draft Criminal Law (Penal Code) which is more familiar maximum penal provision . The results showed that the minimum pinadana special provisions in the law of corruption can be breached so long as the judge has the legal resening or residenti proper ratio to a corruption case by looking at the size scale of the corruption case with consideration and interpretation of the patterns perspective, social - justice, moral justice and community justice decision was taken to drop the minimum punishment. Criminal punishment under the criminal provisions of the special minimum in some court decisions can be made by several criteria into consideration the provisions of the criminal judges deviate minimum, the criteria of the element of state assets or state economy as a result of the acts of corruption tiundak and criteria of the role and position of the defendant in acts of corruption. Keywords: Interpretation of judges , a special minimum criminal , corruption